Customers acceptance on BTC Bakery single bun from 4P's perspectives / Amal Nur Hurul Ain Abdul Rahman - Abdul Rahman, Amal Nur Hurul Ain (2015)
This study was conducted to get a general overview on the level of customer acceptance towards the BTC Bakery Single Bun that being measures from the 4Ps Perspectives. This research paper is conducted by doing the survey which is using the questionnaires as a medium in gathering data. It involved of 110 respondents that consist of the Customer of BTC Bakery within the area of Sepanggar, Kota Kinabalu, Sabah. The instrument used in collecting data is by using a Likert - Scale questionnaires that have been design by the researchers itself. This research paper is using the Statistical Package for Social Science (SPSS) Version 21. The data can be trust as the reliability of the questionnaires reaches .759 and the results showed that the Customer Acceptance towards the BTC Bakery Single Bun can be improve. Thus, the researchers have done a few recommendations towards the organizations just to give some idea upon their marketing strategies based on 4Ps Perspectives which is involved Product, Price, Place (Distribution) and Promotion.